1989
DOI: 10.1007/bf02577379
|View full text |Cite
|
Sign up to set email alerts
|

Arteriographic study of variant arterial anatomy of the upper extremities

Abstract: Anatomic variations in the major arteries of the upper extremities have been reported in 11-24.4% of individuals. In a review of 100 upper extremity arteriograms, we found an overall incidence of 9%. High origin of the radial artery from the brachial artery was the most frequently encountered anomaly occurring in 7% of individuals and accounting for 78% of all anatomic variations. Origin of the radial and ulnar arteries from the axillary artery was an infrequent finding occurring in only 2% of extremities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
86
1
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(91 citation statements)
references
References 7 publications
3
86
1
1
Order By: Relevance
“…Uglietta et al retrospectively reviewed 100 upper extremity arteriograms, and they observed major anatomic variations in the arterial branching pattern in nine (9.0%) of them. In one case (1.0%) the ulnar artery originated from the axillary artery (10). The common interosseous artery taking its origin from a high radial artery or, very rarely, from the normal radial artery has been reported (11,12).…”
Section: Discussionmentioning
confidence: 99%
“…Uglietta et al retrospectively reviewed 100 upper extremity arteriograms, and they observed major anatomic variations in the arterial branching pattern in nine (9.0%) of them. In one case (1.0%) the ulnar artery originated from the axillary artery (10). The common interosseous artery taking its origin from a high radial artery or, very rarely, from the normal radial artery has been reported (11,12).…”
Section: Discussionmentioning
confidence: 99%
“…Anatomic variations in the major arteries of the upper extremities have been reported in 11-24.4% of the individuals [3]. Knowledge on origin, course and distribution of ulnar artery is important, due to its clinical implications.…”
Section: Discussionmentioning
confidence: 99%
“…The reported incidence of superficial ulnar artery arising from the axillary artery varies between 0.7% and 2% [3]. The bilateral presence of superficial ulnar artery, with a different origin on each side, is even more rare [4].…”
Section: Introductionmentioning
confidence: 99%
“…Standard textbooks of anatomy explained that during embryogenesis, the lateral branch of the 7 th cervical inter segmental artery enlarges to form the axial artery of the upper limb which further develops as the axillary and brachial artery, in which the later divides as the radial and ulnar artery [3,4]. Though this is the normal branching pattern of the axillary artery previous research studies documented different types of variations in their branching pattern and course, shows that there is no fixed and standard branching pattern of the axillary artery [5][6][7][8][9][10][11].…”
Section: Imentioning
confidence: 99%